Sex-specific association of visceral adiposity index with renal dysfunction in chinese type 2 diabetes: A cross-sectional study - Songfang Liu; Louyan Ma; Yu Niu; Ranran Ma; Ting Qi; Bingyin Shi (PLoS ONE, 2026)
Background Diabetic nephropathy is a serious microvascular complication of type 2 diabetes mellitus, yet the sex-specific relationship between visceral adiposity and renal dysfunction remains insufficiently explored in Chinese populations. Objective To investigate the association between visceral adiposity indices and renal dysfunction in Chinese type 2 diabetes mellitus patients, emphasizing this population’s unique risk profile and the clinical utility of composite adiposity measures. Methods This cross-sectional study involved 1,335 type 2 diabetes mellitus patients. The primary outcome variable was renal dysfunction, defined as an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m². Thirteen visceral adiposity indices were evaluated through correlation analysis, overall population regression modeling, and sex-stratified approaches. Multiple regression models were progressively adjusted for demographic characteristics, lifestyle factors, clinical parameters, and medications to assess independent associations with estimated glomerular filtration rate. Results The study population (median age: 54 years; 67.04% male) demonstrated distinct characteristics between estimated glomerular filtration rate groups. The estimated glomerular filtration rate decline group exhibited significantly higher age, blood pressure, and fasting glucose compared to the normal group (all p < 0.05). Despite similar body mass index levels, multiple visceral adiposity indices (waist-to-hip ratio, lipid accumulation product, Chinese visceral adiposity index, visceral adiposity index, body roundness index, relative fat mass, and metabolic score for visceral fat) were significantly elevated in the eGFR Decline Group. Comprehensive correlation analysis revealed substantial attenuation after confounder adjustment, with only visceral adiposity index maintaining significance in the total population (adjusted r = −0.075, p = 0.007). Multivariate regression confirmed visceral adiposity index as the most robust predictor (β = −1.63, 95% CI: −2.75 to −0.50, p = 0.0048). Sex-stratified analyses revealed profound differences: visceral adiposity index demonstrated independent predictive value exclusively in males (β = −2.41, 95% CI: −3.84 to −0.98, p = 0.001), while all female associations became non-significant after full adjustment. Conclusion Visceral adiposity index showed strong and consistent associations with renal dysfunction specifically in Chinese male T2DM patients, while female associations were primarily mediated through confounding pathways. These findings highlight critical sex-specific differences and support the integration of composite visceral adiposity indices into routine clinical assessment for male diabetic patients, emphasizing the necessity of population-specific and gender-tailored approaches in renal risk stratification.